Determination of the elemental composition of ferromanganese formations certified reference materials by mass-spectrometry with inductively coupled plasma - N. V. Zarubina; M. G. Blokhin; P. E. Mikhailik; A. S. Segrenev (Стандартные образцы, 2017)
Contents of 41 elements in the Russian standard samples of ferromanganese nodules OOPE 601, OOPE 602, OOPE 603 and ore crust OOPE 604 were identified by mass-spectrometry with inductively-coupled plasma. Content of W was firstly presented in the sample OOPE-603. Relative standard deviation for most elements was in the range of 3-10%. A description of ICP-MS technique including sample preparation procedure and other instrumental parameters were given as well as analysis of ferromanganese nodules standard samples NOD-A-1 and NOD-P-1 of U.S. Geological Survey was demonstrated for validation. Normalized to chondrite distribution curves of REE in the studied samples were shown as an indicator of the internal consistency offound concentrations. The available literature data on the content of a wide range of elements and its comparison with the matter obtained by us was produced. Measured contents of elements in the established CRM may be useful in the analytical practice to evaluate precision of results. There is a lack of relevant information on a variety of geochemically important elements in the Russian standard samples of OOPE series and the new data can be taken into account in their certification.